O homo ecranis e a introdução de novas linguagens: um estudo sobre o iPad como múltiplas plataformas de leitura - Cattani, Deborah (Revista Extraprensa, 2013)
This paper intends to investigate the possible emergence of a new kind of reading: information acquisition through tactile input. The rise of tablets in the digital market, mainly the Apple´s iPad, has led users to develop new habits and languages. This research develops from an online questionnaire for iPad,users, as well as from news related to the subject. After the initial stage of data collection, these latent categories become the basis for further analysis.